The Dynamics of Political Communication in the Digital Age: Challenges and Opportunities - Nanang Kurniawan; Ayu Larasati (Jurnal Indonesia Sosial Sains, 2026)
The rapid development of digital technology has brought profound changes in various aspects of life, including in political communication. In the digital age, digital platforms and social media play an increasingly important role in shaping public opinion, spreading political messages, and strengthening the relationship between politicians and voters. This article aims to examine the dynamics of political communication in the digital age, by highlighting the various challenges and opportunities that arise along with the adoption of new technologies in the political space. Through a qualitative approach, this study analyzes various case studies related to the use of social media in political campaigns, its influence on the democratic process, and its impact on social polarization and disinformation.  The findings of the study show that while digital technology accelerates the dissemination of political information and allows for greater public involvement in political discourse, it also poses serious challenges. One of the main challenges is the rapid and uncontrolled spread of disinformation, which can affect the integrity of the political process and undermine public trust in political institutions. In addition, social polarization is increasingly evident due to the tendency of individuals to be trapped in 'echo chambers'—conversations that reinforce personal views and ignore other perspectives. This phenomenon is exacerbated by digital platform algorithms that tend to show content that matches user preferences, thus exacerbating social tensions. However, digital platforms also offer inclusive political participation, free expression, and greater transparency, which can strengthen public accountability.